Treatment of 1,10-phenanthroline laboratory wastewater using the solar photo-Fenton process - Apolinario da Silva, Milady Renata; Trovo, Alam Gustavo; Pupo Nogueira, Raquel Fernandes (Elsevier B.V., 2007)
The red Fe2+-phenanthroline complex is the basis of a classical spectrophotometric method for determination of iron. Due to the toxicity of this complexing agent, direct disposal of the wastewaters generated in analytical laboratories is not environmentally safe. This work evaluates the use of the solar photo-Fenton process for the treatment of laboratory wastewaters containing phenanthroline. Firstly, the degradation of phenanthroline in water was evaluated at two concentration levels (0.1 and 0.01%, w/v) and the efficiencies of degradation using ferrioxalate (FeOx) and ferric nitrate were compared. The 0.01% w/v solution presented much higher mineralization, achieving 82% after 30 min of solar irradiation with both iron sources. The solar photo-Fenton treatment of laboratory wastewater containing, in addition to phenanthroline, other organic compounds such as herbicides and 4-chlorophenol, equivalent to 4500 mg L-1 total organic carbon (TOC) resulted in total degradation of phenanthroline and 25% TOC removal after 150 min, in the presence of either FeOx or ferric nitrate. A ratio of 1: 10 dilution of the residue increased mineralization in the presence of ferrioxalate, achieving 38% TOC removal after 120 min, while use of ferric nitrate resulted in only 6% mineralization over the same period. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: advanced oxidation processes; ferrioxalate; iron complexes; laboratory wastewater